Características estruturais e composição bromatológica do capim Marandu submetido a duas alturas de resíduo - Almeida, Cleverton Marcelino de (2013)
This study aimed to evaluate the influence of two heights of residue in the structural and chemical composition of Brachiaria brizantha. Palisade. The experiment was conducted at the Experimental Farm of the Federal University of Mato Grosso , in Santo Antônio de Leverger between April to July 2012. The treatments consisted of two heights residue with 7 repetitions, totaling 14 experimental units in a randomized experimental design. In turn, each portion had an area of 8 m2 (4 x 2 m). The variables analyzed were: final length of leaf blade (CFLV), length of the fakeculm (CC), number of leaves (NFV ), total forage dry matter (MSFT), dry weight of leaf blade (MSLV), mass dry green stalk (MSCV), percentage of green leaf blades in total (%LAM), stem percentage of total dry matter (%COL), relative leaf blade:stem (LFV:C), dry matter (MS), mineral matter (MM), organic matter (MO), crude protein (PB), neutral detergent fiber (FDN), neutral detergent fiber indigestible (FDNi), acid detergent fiber (FDA), total gas volume (mL) and digestion rate (h- 1). There were significant differences (P< 0,01) between the heights of waste for variables CFLV, CC, MSFT, MSLV, MSCV, PB, FDA, MM, MO and %LAM (P<0,05). The greater height of residue gave higher dry fodder, because of the greater length of the leaf blade and fakeculm. In contrast, the lower height gave higher percentages of leaf blade, ensuring greater sward renovation.